Use of CT colonography in the English Bowel Cancer Screening Programme. Issue 6 (16th August 2013) - Plumb, Andrew A; Halligan, Steve; Nickerson, Claire; Bassett, Paul; Goddard, Andrew F; Taylor, Stuart A; Patnick, Julietta; Burling, David
Abstract : Objective: To examine use of CT colonography (CTC) in the English Bowel Cancer Screening Programme (BCSP) and investigate detection rates. Design: Retrospective analysis of routinely coded BCSP data. Guaiac faecal occult blood test (gFOBt)-positive screenees undergoing CTC from June 2006 to July 2012 as their first-line colonic investigation were included. Abnormalities found at CTC, subsequent polyp, adenoma and cancer detection and positive predictive value (PPV) were calculated. Detection rates were compared with those observed in gFOBt-positive screenees investigated by colonoscopy. Multilevel logistic regression was used to examine factors associated with variable detection. Results: 2731 screenees underwent CTC. Colorectal cancer (CRC) or polyps were suspected in 1027 individuals (37.6%; 95% CI 33.8% to 41.4%); 911 of these underwent confirmatory testing. 124 screenees had CRC (4.5%) and 533 had polyps (19.5%), 468 adenomatous (17.1%). Overall detection was 24.1% (95% CI 21.5% to 26.6%) for CRC or polyps and 21.7% (95% CI 19.2% to 24.1%) for CRC or adenoma. Advanced neoplasia was detected in 504 screenees (18.5%; 95% CI 16.1% to 20.8%). PPV for CRC or polyp was 72.1% (95% CI 66.6% to 77.6%). By comparison, 9.0% of 72 817 screenees undergoing colonoscopy had cancer and 50.6% had polyps; advanced neoplasia was detected in 32.7%. CTC detection rates and PPV were higher at centres with experienced radiologists (>1000 examinations) and at high-volume centres (>175 cases/radiologist/annum). Centres using three-dimensional interpretation detected more neoplasia. Conclusions: In the BCSP, detection rates after positive gFOBt are lower for CTC than colonoscopy, although populations undergoing the two tests are different. Centres with more experienced radiologists have higher detection and accuracy. Rigorous quality assurance of BCSP radiology is needed.